2007
DOI: 10.1073/pnas.0611008104
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of growth hormone-releasing hormones and receptors in nonmammalian vertebrates

Abstract: In mammals, growth hormone-releasing hormone (GHRH) is the most important neuroendocrine factor that stimulates the release of growth hormone (GH) from the anterior pituitary. In nonmammalian vertebrates, however, the previously named GHRH-like peptides were unable to demonstrate robust GH-releasing activities. In this article, we provide evidence that these GHRH-like peptides are homologues of mammalian PACAP-related peptides (PRP). Instead, GHRH peptides encoded in cDNAs isolated from goldfish, zebrafish, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 49 publications
(36 reference statements)
6
59
0
Order By: Relevance
“…Consistent results have also been reported in fish, such as catfish (Ictalurus punctatus) (McRory et al, 1995), zebrafish (Danio rerio) (Fradinger and Sherwood, 2000) and salmon (Parker et al, 1997). Recent research has indicated that GHRH-like peptides were homologues of mammalian PACAP-related peptides, whereas, genes encoding only GHRH peptides were identified in goldfish (Carassius auratus), zebrafish (D. rerio), and African clawed frog (Xenopus tropicalis) (Lee et al, 2007). Moreover, the cDNAs encoding PRP/PACAP and GHRH in half-smooth tongue sole were also cloned, respectively (Ji et al, 2011).…”
Section: Introductionsupporting
confidence: 53%
“…Consistent results have also been reported in fish, such as catfish (Ictalurus punctatus) (McRory et al, 1995), zebrafish (Danio rerio) (Fradinger and Sherwood, 2000) and salmon (Parker et al, 1997). Recent research has indicated that GHRH-like peptides were homologues of mammalian PACAP-related peptides, whereas, genes encoding only GHRH peptides were identified in goldfish (Carassius auratus), zebrafish (D. rerio), and African clawed frog (Xenopus tropicalis) (Lee et al, 2007). Moreover, the cDNAs encoding PRP/PACAP and GHRH in half-smooth tongue sole were also cloned, respectively (Ji et al, 2011).…”
Section: Introductionsupporting
confidence: 53%
“…These fish ghrhs are expressed at high levels in the hypothalamus, telencephalon, spinal cord, and at a relative low level in the ovary. Similarly, their specific receptors, ghrh-rs, are abundant in the hypothalamus, telencephalon, spinal cord, diencephalon, and pituitary, but only present at low levels in the ovary [44,47]. Based on our recent pituitary transcriptome studies, the levels of both ghrh and ghrh-r expression were less than 1 RPKM in the zebrafish pituitary at both 45 and 90 d post-fertilization (dpf) [48].…”
Section: Growth Hormone-releasing Hormone (Ghrh)mentioning
confidence: 99%
“…The 27-aa fish GHRH mature peptides exhibit 81.5% homology with human GHRH [44]. Until recently, the GHRH/ GHRH-R system has only been documented in a few teleostean species, including zebrafish, goldfish, olive flounder, Fugu, medaka, rainbow trout, half-smooth tongue sole, and orange-spotted grouper [44][45][46][47]. These fish ghrhs are expressed at high levels in the hypothalamus, telencephalon, spinal cord, and at a relative low level in the ovary.…”
Section: Growth Hormone-releasing Hormone (Ghrh)mentioning
confidence: 99%
“…12) Recently, non-mammal GHRH peptides encoded in cDNAs isolated from goldfish, zebrafish, and frog were identified. 13) In the goldfish, a 4-h incubation of pituitary cells with increasing doses (0.1 nM-1 mM) of goldfish GHRH resulted in a dose-dependent increase in GH release, the minimum effective dose being 10 nM. 13) Like GHRH, PACAP 38 (0.1 nM-1 mM) was also effective in inducing GH release from both goldfish and grass carp perifused pituitary cells in a dose-dependent manner.…”
mentioning
confidence: 99%
“…13) In the goldfish, a 4-h incubation of pituitary cells with increasing doses (0.1 nM-1 mM) of goldfish GHRH resulted in a dose-dependent increase in GH release, the minimum effective dose being 10 nM. 13) Like GHRH, PACAP 38 (0.1 nM-1 mM) was also effective in inducing GH release from both goldfish and grass carp perifused pituitary cells in a dose-dependent manner. 6,7) These findings indicate that both PACAP and GHRH are y To whom correspondence should be addressed.…”
mentioning
confidence: 99%